2021
DOI: 10.1002/app.50601
|View full text |Cite
|
Sign up to set email alerts
|

A nano‐Fe3O4 material coated with AM/AMPS copolymer for viscosity enhancement at harsh reservoir conditions

Abstract: A Fe 3 O 4 nonaparticles coated with acrylamide/2-acrylamido-2-methyl-1-propanesulfonic acid copolymer(Fe 3 O 4-Polymer NPs) was synthesized by emulsion polymerization. The structure of Fe 3 O 4-Polymer NPs was then characterized by infrared spectroscopy, thermo-gravimetric analysis, and scanning electron microscopy. Meanwhile, the rheological properties of Fe 3 O 4-Polymer NPs solution were systematically studied. The results showed that when dosage of hydrophobic Fe 3 O 4-Oleic NPs is 10%, the synthesized Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…In contrast, the absorption peak at 1650-1600 cm -1 , corresponding to olefinic stretching in acrylamide and N-vinylpyrrolidone units, disappeared in the PCM spectrum. These disappearances prove that the monomers have been completely consumed following the reaction [21]. Thus, the FTIR spectrum exhibited all the component signals in the structure of the Fe 3 O 4 -core/(AM-NVP) copolymer-shell NPs.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…In contrast, the absorption peak at 1650-1600 cm -1 , corresponding to olefinic stretching in acrylamide and N-vinylpyrrolidone units, disappeared in the PCM spectrum. These disappearances prove that the monomers have been completely consumed following the reaction [21]. Thus, the FTIR spectrum exhibited all the component signals in the structure of the Fe 3 O 4 -core/(AM-NVP) copolymer-shell NPs.…”
Section: Resultsmentioning
confidence: 82%
“…The process of polymerisation of oleic-acid-surface modified nano-oxide cores with acrylamide (AM) and 2-acrylamido-2-methylpropane sulfonic acid (AMPS) monomers has been described in detail [20,21], where the polymers were grafted onto the particle surface by polymerising vinyl monomers with the vinyl linkage of oleic acid. The obtained results showed that (AM-AMPS) copolymer coated NP-based nanofluids affected the EOR capacity, such as a viscosity enhancement, increase in the displacement efficiency, thermal stability, and salt resistance at 90 °C.…”
Section: Nanoparticles For Eor Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanotechnology, as a cutting-edge technology, has great potential in drilling and completion, , reservoir stimulation, , enhanced oil recovery, , and other oilfield operations. Nanoparticles are ultrafine (1–100 nm), usually larger than atomic clusters, but smaller than ordinary particles.…”
Section: High-temperature-resistant Ves Fracturing Fluidsmentioning
confidence: 99%